Post-transplantation Cyclophosphamide, Tacrolimus and Low-Dose ATG as GVHD Prophylaxis for Allogeneic Peripheral Stem Cell Transplantation for Adult Patients With Lymphoid Malignancies: A Single Arm Phase II Study - Jiang, Jie-ling; Gao, Wen-hui; Wang, Li-ning; Wan, Ming; Wang, Ling; Hu, Jiong (Frontiers in Medicine, 2021)
The PT-Cy was considered as one of the mainstay protocol for graft verus host disease (GVHD) prophylaxis. Recent study demonstrated that PT-Cy combined with other immunosuppressants could further reduce the incidence of GVHD and improve the GVHD and relapse free survival (GRFS). In this prospective phase II study, we evaluated the effect of a new GVHD prophylaxis consist of PT-Cy combined with tacrolimus and low dose anti-thymoglobulin (ATG). A total of 23 patients were enrolled including 20 patients with acute lymphoblastic leukemia (ALL) and 3 patients with T cell lymphoma. The median age was 29 years (range, 16 58 years). Patients with HLA-matched related donor (MSD, n=7) received PT-Cy combined with tacrolimus, while patients with HLA matched unrelated (MUD, n=2) or haplo-identical (Haplo, n=14) donor received additional ATG at 2.5mg/kg on day 15 or day 22 after engraftment of neutrophils. As to the acute GVHD(aGVHD), only 3 patients developed grade I (n=1) or grade II (n=2) aGVHD with 100-day incidence of all aGVHD and II-IV aGVHD at 13.0±5.1% and 9.1±6.1% respectively. Only 2 patients had mild and 1 had moderate chronic GVHD(cGVHD), with 1-year incidence of cGVHD and moderate/severe cGVHD at 15.2±8.7% and 4.6±4.4% respectively. A high incidence of CMV reactivation was documented (14/16 with MUD/Haplo donor and 2/7 with MSD) with only 1 CMV disease documented. There was 2 EBV reactivation without post-transplantation lymphoproliferative disease(PTLD) documented. With a median follow-up of 303 days (range, 75 700 days), 3 patients relapsed leading to 1-year cumulative incidence of relapse (CIR) at 12.8%±9.2%. Only 1 patient died of CMV pneumonia on day 91 with both 100-day and 1-year non-relapse mortality (NRM) at 4.6%±4.4%. The 1-year overall survival (OS), event-free survival (EFS) and GRFS were 95.5%±4.4%, 82.6%±9.5% and 68.0%±11.3% respectively. Based on Simon’s stage II design, our primary data showed that the PT-Cy+tacrolimus±ATG protocol was promising in preventing aGVHD and cGVHD, which may translate into low NRM without increased CIR. Further clinical trial with large number of patients should be warranted. This trial was registered at www.clinicaltrials.gov as #NCT 04118075.